Utilizing an Activity-Based Costing System to Analyze the Logistical Expenses of Commercial Lobster Farms Kalasin District - taengphukieo, Ratchada; Uttra, Savalee; To-on, Piyanat; Nitisiri, Nattanan (Frontiers in Engineering Innovation Research, 2024)
The goal of this research is to Using an activity-based costing system, examine the logistics expenses associated with a variety of commercial farm-based prawn aquaculture activities in the Kalasin province. (Activity-Based Costing: ABC), which employs interviews and field surveys to gather information. The data obtained from in-depth interviews and questionnaires with a sample of 500 farmers who plant giant freshwater prawns for commercial purposes were utilized to calculate activity-based costs. The study’s findings indicate that producers engaged in the commercial cultivation of giant freshwater prawns primarily engage in three activities: 1. Pond preparation and shrimp reproduction; 2. Raising and management activities during raising; and 3. Sales activities. With regard to the activity basic cost of shellfish farming. The total cost of producing gigantic freshwater prawns per rai was determined to be 71,650 baht. The main activity with the highest cost is the activity of preparing rearing ponds and breeding shrimp. The total cost is 41,100 baht per rai, accounting for 57.36 percent. The second is the raising and management activities during raising. The total cost is 23,400 baht per rai, accounting for 32.66 percent, and the third-ranking selling activity is 7,150 baht per rai, accounting for 9.98 percent.